2013
DOI: 10.1007/s12011-013-9854-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Resveratrol Attenuates Serum Catalase, Glutathione Peroxidase, and Element Values in Rats with DMBA-Induced Mammary Carcinogenesis

Abstract: In this paper, a hypothesis was assessed whether or not the intoxication with copper and supplementation with copper plus resveratrol would result in changes in the activities of catalase and glutathione peroxidase and moreover if the characteristic changes would appear in concentrations of copper, iron, calcium, magnesium, and zinc in the serum of rats with chemically induced carcinogenesis. Female Sprague-Dawley rats were divided into study groups which, apart from the standard diet, were treated with copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
(51 reference statements)
0
32
0
Order By: Relevance
“…Copper, as a limiting factor, has multifaceted roles in cancer progression, including growth, angiogenesis and metastasis . Preclinical studies have demonstrated that copper supplementation in rodent models significantly enhanced mammary, pancreatic, and lung cancer growth . In addition, copper can regulate the expression and secretion of angiogenic molecules (e.g., vascular endothelial growth factor [VEGF], interleukin‐1alpha [IL‐1α], and fibroblast growth factors [FGFs]), and enhance the affinity of angiogenic growth factor (i.e., angiogenin) for endothelial cells, and thus promote angiogenesis to nurture the tumor microenvironment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper, as a limiting factor, has multifaceted roles in cancer progression, including growth, angiogenesis and metastasis . Preclinical studies have demonstrated that copper supplementation in rodent models significantly enhanced mammary, pancreatic, and lung cancer growth . In addition, copper can regulate the expression and secretion of angiogenic molecules (e.g., vascular endothelial growth factor [VEGF], interleukin‐1alpha [IL‐1α], and fibroblast growth factors [FGFs]), and enhance the affinity of angiogenic growth factor (i.e., angiogenin) for endothelial cells, and thus promote angiogenesis to nurture the tumor microenvironment .…”
Section: Discussionmentioning
confidence: 99%
“…10 Preclinical studies have demonstrated that copper supplementation in rodent models significantly enhanced mammary, pancreatic, and lung cancer growth. [39][40][41] In addition, copper can regulate the expression and secretion of angiogenic molecules (e.g., vascular endothelial growth factor [VEGF], interleukin-1alpha [IL-1α], and fibroblast growth factors [FGFs]), and enhance the affinity of angiogenic growth factor (i.e., angiogenin) for endothelial cells, and thus promote angiogenesis to nurture the tumor microenvironment. 10,42 Further evidence indicates that copper may directly affect the ability of cancer cells to invade and metastasize through influencing the activities of copper-dependent proteins, such as lysyl oxydase (LOX), lysyl oxydase-like (LOXL) proteins and Memo.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, supplementation of water of pseudopregnant mice with CuSO 4 (198 mg/L) did not show any effect on the incidence of carcinogen-induced lymphomas, lung, ovaries, and breast cancers, which was most probably related to insufficient Cu concentrations in tissues (were not measured) [ 70 ]. Moreover, several studies demonstrated that supplementation of food and water with Cu salts has stimulated tumor progression [ 57 , 71 , 72 , 73 ]. When rats were given food with CuSO 4 (42.6 mg Cu/kg food) with or without antioxidant resveratrol, the carcinogen-induced mammary carcinogenesis was markedly accelerated [ 71 , 72 ].…”
Section: Tumor Modulation With Inorganic Cu Saltsmentioning
confidence: 99%
“…Moreover, several studies demonstrated that supplementation of food and water with Cu salts has stimulated tumor progression [ 57 , 71 , 72 , 73 ]. When rats were given food with CuSO 4 (42.6 mg Cu/kg food) with or without antioxidant resveratrol, the carcinogen-induced mammary carcinogenesis was markedly accelerated [ 71 , 72 ]. This process was accompanied by the significant increase of serum Cu and decrease of serum Fe and Zn/Cu ratio similar to those observed in breast cancer patients [ 74 , 75 ].…”
Section: Tumor Modulation With Inorganic Cu Saltsmentioning
confidence: 99%
“…Myricetin proved the capacity of flavonols to act as antioxidant in cells definitely represents a potential in the field of oncology. [ 23 24 25 26 27 ]…”
Section: Discussionmentioning
confidence: 99%